MiR‐1827 functions as a tumor suppressor in lung adenocarcinoma by targeting MYC and FAM83F. Issue 2 (8th October 2019) - Fan, Gongchun; Xu, Peng; Tu, Peng
Abstract: The bioactivity of microRNA‐1827 (miR‐1827) in lung adenocarcinoma cells would be explored. The expression level of gene and miR‐1827 in 76 pairs of lung adenocarcinoma tissues and adjacent counterparts were analyzed by a quantitative real‐time polymerase chain reaction. Primary lung adenocarcinoma cells were derived from patients' tissues. These cells were treated with miR‐1827 agomir to mimic the upregulation of endogenous miR‐1827. The malignant degree of lung adenocarcinoma cells in vitro was evaluated by cell proliferation, colony formation, transwell invasion, and apoptosis assays. Western blot analysis was used to observe the transition of lung adenocarcinoma cells from epithelial‐to‐mesenchymal. Target genes of miR‐1827 were predicted by bioinformatics analysis. In addition, the interaction between miR‐1827 and candidate messenger RNAs was verified by dual‐luciferase reporter assay and AGO2‐RNA immunoprecipitation. Besides, the effect of miR‐1827 on tumors was verified by in vivo experiments. Transient gene overexpression was achieved by plasmids transfection. In this study, we found that the expression of miR‐1827 was downregulated in lung adenocarcinoma, and its low expression was significantly correlated with the progression of lung adenocarcinoma and poor prognosis of patients. miR‐1827 overexpression remarkably reduced the malignancy of primary lung adenocarcinoma cells in vitro. MYC and FAM83F were identified as two targeted genes of miR‐1827 in lung adenocarcinoma cells. The levels of these two genes were upregulated in lung adenocarcinoma, and their high expression was significantly associated with the progression of lung adenocarcinoma and poor prognosis of patients. Overexpression of MYC or FAM83F attenuated the effects of miR‐1827 on primary lung adenocarcinoma cells in vitro. In addition, in vivo experiments showed that miR‐1827 inhibited tumor growth by reducing the levels of MYC and FAM83F. In conclusion, miR‐1827 might repress the development of lung adenocarcinoma by targeting oncogenic genes MYC and FAM83F. Abstract : we found that miR‐1827 might reduce lung adenocarcinoma progression by targeting MYC and FAM83F. Treatment with miR‐1827 agomir might improve the therapeutic outcome of lung adenocarcinoma and patients' prognosis.